Do information and communication technologies influence skills, competencies, health and well-being of teenagers? Current evidence - Lim, Willone; Theng Lau, Bee; Chua, Caslon; Amirul Islam, Fakir M (EAI Endorsed Transactions on Pervasive Health and Technology, 2021)
INTRODUCTION: Information and Communication Technologies are deemed to be a significant influence on teenagers’ development. It is important for studies to be conducted to assess the underlying influence of ICT on the teenager age group.OBJECTIVES: The aim of this paper is to review whether ICT influences teenagers’ skills, competencies, health and well-being based on previous studies.METHODS: Articles from 2015 to 2020 were selected for analysis to identify the influences on teenagers.RESULTS: Computer and mobile devices offer opportunities to improve literacy in digital skills and competencies. It is also evident that teenagers are prone to risks of getting musculoskeletal symptoms as a result of excessive use of such devices, and it also leads to unforeseen illnesses such as depression in the case of teenager’s well-being.CONCLUSION: Adopting ICT may have beneficial implications for teenagers, but it can pose more adverse effects on their development when used excessively.
Keywords: Information and communication technology; skills; competencies; health; well-being; influence; teenager